Baby Trouble in the Last Best West : Making New People in Alberta, 1905-1939 - Kaler, Amy, 1966- (Book collections on Project MUSE., 2016)
"Reproduction is the most emotionally complicated human activity. It transforms lives but it also creates fears and anxieties about women whose childbearing doesn't conform to the norm. Baby Trouble in the Last Best West explores the ways that women's childbearing became understood as a social problem in early twentieth-century Alberta. Kaler utilizes censuses, newspaper reports, social work case files, and personal letters to illuminate the ordeals that women, men, and babies were subjected as Albertans debated childbearing. Through the lens of reproduction, Amy Kaler offers a vivid and engaging analysis of how colonialism, racism, nationalism, medicalization, and evolving gender politics contributed to Alberta's imaginative economy of reproduction. Kaler investigates five different episodes of "baby trouble" including: the emergence of obstetrics as a political issue, the drive for eugenic sterilization, unmarried childbearing and "rescue homes" for unmarried mothers, state-sponsored allowances for single mothers, and high infant mortality. Baby Trouble in the Last Best West will transport the reader to the turmoil of Alberta's early years while examining the complexity of settler society-building and gender struggles."--